(untitled) (PerCursos, 2025)
This essay examines sport and technique within neoliberal capitalism as arenas where biopolitics is manifested. It starts from the premise that sport is the space par excellence for the materialization of the modern body, where the techno-scientific regulation of life—aimed at maximizing performance—is revealed in full clarity. The central concern lies in the dangers of a technical rationality that operates relatively autonomously, detached from philosophical inquiry, and governed almost solely by the ideal of efficiency. We face a race already lost between technical, technological, and biotechnological advances on one hand, and the demand for meaning in the face of bodily interventions in elite sport on the other. Yet, the space of critical thought and political action remains open. The essay concludes that, in an increasingly spectacularized and spectacularizing sporting culture—unhesitant in intervening in molecules, hormones, and chromosomes—the administration and bureaucratization of organic life overshadow philosophical and political reflection, itself progressively shaped by neoliberal logic.